Relationship Between Food Service Satisfaction and Macronutrient Intake With Nutritional Status of Patients at DKT TK IV 02.07.04 Hospital Bandar Lampung - Dian Kirana; Ai Kustiani; Dewi Woro Astuti (AR-RUMMAN: Journal of Education and Learning Evaluation, 2024)
Malnutrition affects 13-69% of people receiving care in hospitals worldwide. Anthropometric examinations reveal that 50% of patients in hospitals suffer from malnutrition. Patient psychology during the healing process is affected by a number of factors, including the patient's level of satisfaction with the hospital food service. The purpose of this study was to determine how the nutritional health of patients at DKT Hospital Bandar Lampung is related to satisfaction with food service and macronutrient consumption. This study uses a cross-sectional strategy as a design or analytical observational research plan. The sample used in this study was 47 respondents selected using the simple random sampling method. The bivariate test used in this study is the Chi-Square test. The results showed that there was a relationship between food service satisfaction and patient nutritional status (p-value = 0.013) and there was a relationship between macronutrient intake and patient nutritional status (energy = 0.023, protein = 0.035, fat = 0.021, carbohydrates = 0.045). Based on the results of the study, it can be concluded that there is a significant relationship between food service satisfaction and macronutrient intake with the nutritional status of patients at DKT TK IV hospital 02.07.04 Bandar Lampung.